Correction: Mølvig et al. Terahertz Cross-Correlation Spectroscopy and Imaging of Large-Area Graphene. Sensors 2023, 23, 3297 - Bjørn Hübschmann Mølvig; Thorsten Bæk; Jie Ji; Peter Bøggild; Simon Jappe Lange; Peter Uhd Jepsen (Sensors)
In the original publication [...]